(untitled) (Chemical Engineering Research Bulletin, 2010)
Corrosion inhibition of mild steel by sodium nitrite in simulated cooling water (SCW) containing chloride ion was investigated. Electrochemical techniques such as corrosion potential (Ecorr) measurement and potentiodynamic sweep experiments were used. The experimental parameters were concentration of the inhibitor, pH of the aqueous media and soaking time. Nitrite inhibited mild steel corrosion in near neutral and alkaline (pH 6 and above) SCW and accelerated corrosion in acidic media (pH 4 and below). Inhibition activity increased with the increase of nitrite concentration up to 500 ppm, and afterwards remained more or less constant at pH 6 and above. In stagnant SCW, maximum corrosion inhibition was observed at pH 8 for all concentration of NaNO2. Inhibition action of NaNO2 was found to increase with the increase of soaking time up to 24 hours, and afterwards it remained more or less constant at all nitrite concentrations at and above pH 6. Based on the experimental results, mechanisms of action of NaNO2 on mild steel corrosion inhibition in SCW have been proposed. Keywords: Corrosion; Potentiodynamic sweep; Inhibitor DOI = 10.3329/cerb.v14i2.4813 Chemical Engineering Research Bulletin 14 (2010) 87-91